META-ANALYSIS OF THE INFLUENCE OF GROUP INVESTIGATION TYPE COOPERATIVE MODELS ON STUDENT’S COMPETENCE IN PHYSICS LEARNING - Rizki Anisa Tanjung; Festiyed Festiyed; Tantri Mayasari (PILLAR OF PHYSICS EDUCATION, 2022)
Various studies related to the influence of group investigation type cooperative models on student competence have been widely conducted. Researchers are interested in conducting meta-analysis research to summarize various studies on the influence of this type of group investigation cooperative model. After the study, researchers concluded that this cooperative model of group investigation type is very effectively applied at the junior high level and effective at the high school level. The influence of cooperative models of group investigationtypes p there are physics subject matter also has a high positive influence for 8 subject matter, namely circular motion, momentum and impulse, static electricity, dynamic fluid, static fluid, kinetic theory of gases, light and optics, vibrations and waves, and dynamic and ineffective electricity on subject matter magnitude and measurement, straight motion, Newton's laws, effort and energy, temperature and heat, rotational dynamics and rigid equilibrium of objects, and elasticity. This group investigation type cooperative model is also able to improve students' competence on changes in concepts, attitude skills, procedural abilities, and generic skills compared to students' cognitive learning outcomes and conceptual knowledge.